State of readiness: National health insurance implementation in hospitals, Gauteng province - Mudzweda, Aluwani D.; Simbeni, Thembi V.; Mogale, Ntlogeleng M. (Curationis (Pretoria), 2025)
Background Most nations are implementing the National Health Insurance (NHI) programme to achieve universal health coverage (UHC). In South Africa, the government is working to ensure everyone has access to healthcare and achieve the UHC goal. Challenges in healthcare facilities include inadequate infrastructure, a lack of personnel and a lack of equipment. Researchers have concentrated on the healthcare practitioner’s awareness of the implementation of NHI compared to their state of readiness even though there have been few studies on the readiness for NHI implementation in South Africa. Objectives The study explored the opportunities and challenges for healthcare facilities in the readiness for the implementation of NHI. Method A non-experimental, quantitative, descriptive, cross-sectional design was employed in this study. The researcher utilised a questionnaire with closed and open-ended questions to obtain information about the state of readiness. The Microsoft Excel spreadsheet was imported to STATA 17 SE software for data analysis. Results In total, 352 healthcare practitioners (HCPs) were recruited with a response rate of 93%. The HCPs (36.2%) were skilled and well-trained to function under NHI in their facilities. The main challenges in health facilities were shortage of staff (20.3%), followed by infrastructure (16.3%). Conclusion This study suggests that there is a need for training and information sharing on the NHI policy. Contribution The study indicates that challenges related to the healthcare system and the success of NHI, among others, are poor infrastructure, shortage of personnel and inadequate resources such as supply.